La Política criminal en los menores adolescentes en Colombia (2017)
The criminal policy of teenagers in Colombia must be approached from a legal and social perspective, due to the high rates of minors’ offenders who engage in criminal behavior; for that reason is of the utmost importance to study the repercussions that they generate for the solution of the contingences that have the minors’ adolescents in the country, especially those that are generated in low strata, where daily altercations and other criminal behaviors are presented such as theft, rape and extortion, which involve minors as perpetrators of punishable conduct.These problems are exacerbated by school drop-out, lack of student interest in entering the school, and illiteracy in criminal groups, which in most cases recruit children who are in difficult economic situations, who see in easy money a solution to their problems.The Colombian State in benefit of providing a legal security and well-being to thecountry’s teenagers, sets a criminal policy that seeks to counteract illegal practices that harm society and protect the rights of Colombian citizens.